"The joint labours of ingenious men": John Smeaton's Royal Society network and the Eddystone Lighthouse. (14th June 2021) - Morris, Andrew M. A.
Abstract: The Industrial Enlightenment is widely thought to have been a period when "science" and "technology" became intimately intertwined. In his 1791 book on the building of the Eddystone lighthouse (completed in 1759), the English engineer John Smeaton praised the Royal Society for being more than a group of abstract theoreticians. This article looks at the fellows of Smeaton's Royal Society network who contributed knowledge, reports, specimens, and inventions solicited by Smeaton when he was working on this lighthouse project. I show, in line with other recent research on this topic, that the "artisans" of the 18th century did not confine themselves to practical know‐how, and that "scholars" were not merely interested in abstract philosophising; instead, the figures I look at in this paper were hybrid knowers who possessed useful knowledge and book learning. I argue that the advice solicited by Smeaton during the building of the lighthouse was characterised not by exchanges between theory and practice, but by a combining of different types of knowledge from separate fields. A second feature of this intellectual co‐operation is that it was not centred on a group of practical industrialists or engineers, but rather it was the Royal Society that served as the common denominator, bringing all of the characters in our story into contact with each other. This is reflected in the subject matter involved, which was characteristic of the research focus of the virtuoso tradition in the 18th‐century Royal Society. Smeaton's contact with this tradition was influenced by his friendships, his social activities, and, indirectly, by the way that the dissensions that occupied the Royal Society during the early 1780s impacted his retrospective account of the project.